The primary somatosensory cortex largely contributes to the early part of the cortical response elicited by nociceptive stimuli - Valentini, E.; Hu, L.; Chakrabarti, B.; Hu, Y.; Aglioti, S.M.; Iannetti, G.D. (NeuroImage (Orlando, Fla.), 2012)
Research on the cortical sources of nociceptive laser-evoked brain potentials (LEPs) began almost two decades ago (Tarkka and Treede, 1993). Whereas there is a large consensus on the sources of the late part of the LEP waveform (N2 and P2 waves), the relative contribution of the primary somatosensory cortex (S1) to the early part of the LEP waveform (N1 wave) is still debated. To address this issue we recorded LEPs elicited by the stimulation of four limbs in a large population (n=35). Early LEP generators were estimated both at single-subject and group level, using three different approaches: distributed source analysis, dipolar source modeling, and probabilistic independent component analysis (ICA). We show that the scalp distribution of the earliest LEP response to hand stimulation was maximal over the central-parietal electrodes contralateral to the stimulated side, while that of the earliest LEP response to foot stimulation was maximal over the central-parietal midline electrodes. Crucially, all three approaches indicated hand and foot S1 areas as generators of the earliest LEP response. Altogether, these findings indicate that the earliest part of the scalp response elicited by a selective nociceptive stimulus is largely explained by activity in the contralateral S1, with negligible contribution from the secondary somatosensory cortex (S2). [Display omitted] ► We used 64-channel EEG in 35 subjects to investigate the earliest LEP sources. ► The earliest hand-LEP topography is maximal over contralateral central electrodes. ► The earliest foot-LEP topography is maximal over the midline central electrodes. ► These topographies are compatible with a generator in S1. ► Hand and foot areas of S1 generate the largest part of the earliest LEP response.